Las tics en la enseñanza y aprendizaje de la matemática, en los estudiantes de primero de bachillerato de la unidad educativa del milenio Penipe, cantón Penipe, periodo 2015-2016. - Cujilema Cujilema, Norma Verónica (2016)
The following work is focused on determining the way ITCs are used in Teaching- Learning of Mathematics, in the students of First year of the Educational Unit of the Millennium Penipe, in the period 2015-2016. This research is quantitative and descriptive. Methods and techniques were applied to be evaluated by means of, scales of valuation, observation tokens, which in turn serve as instruments of data collection that was applied to 66 students. This information was analyzed in Microsoft Excel 2016, using techniques of Descriptive statistics. At the end of the process we obtain the following results of students who use the ITCs in their academic training almost always use tools that help them to promote learning as a conclusion it is important to mention that the use of Tics as tools facilitate the construction of knowledge through games, allowing active participation in the educational process, which encourage students to participate and demonstrate their skill for that reason it is recommended to strengthen the cognitive ability of the students of first year of high school through dynamic, playful and sequenced activities due to it allows students to be part of the learning process.